Triticale in diets for broilers - Zanotto, Dirceu Luís; Guidoni, Antônio Lourenço; Rosa, Paulo Sérgio; Lima, Gustavo Júlio Melo Monteiro de; Viola, Eduardo Spilari; Rabenschlag de Brum, Paulo Antônio (Pesquisa Agropecuaria Brasileira, 2000)
A study was carried out to determine the best replacement level of corn by triticale in diets for broilers. A total of 1,560 one-day old birds, both male and female, were used in the study from 1 to 42 days of age. The experimental design was in random blocks with five treatments: 0, 25, 50, 75% of replacement of corn by triticale, and a fifth diet containing basically triticale and soybean meal. There were 12 replicates per treatment, six with males and six with females. All diets were isocaloric and isoproteic. There was an effect of sex (P < 0.05) for all studied variables, except feed conversion during the first phase of the experiment. Males showed better performance than females. The interaction between sex and treatment was not significant (P > 0.05). According to the results, it is possible to replace up to 75% of corn by triticale, without negatively affect the performance of broilers. The use of triticale will be economically possible for broiler of both sexes, when its cost represents 63, 46 and 45% of price of corn, for substitution levels of 25, 50 and 75%, respectively. Although showing worst performance, total substitution of corn by triticale is advantajous if triticale price is up till 42% corn price.